Reproducible automated renewable column generation. Issue 5 (23rd March 2020) - Metzger, Shalina C.; Ticknor, Brian W.; Tevepaugh, Kayron N.; Bostick, Debra A.; McBay, Eddy H.; Field, M. Paul; Kim, Hwan; Hexel, Cole R.
ABSTRACT: Preparation of chromatographic columns requires considerable time during chemical separation procedures. Automated systems capable of repeatedly generating renewable, uniformly packed columns would find widespread use in analytical laboratories. Here, a fully automated commercial-off-the-shelf (COTS) system was utilized to pack and unpack 1 mL TEVA and UTEVA columns. To accurately determine the reproducibility of the resin load per column, studies were conducted over several weeks. Method optimization yielded an improvement in loading from 15–19% to 3–5% relative standard deviation. Availability of automated COTS equipment capable of reproducibly generating separation columns has the potential to reduce time and costs associated with column separation.